UNDERSTANDING LIVESTREAMING SHOPPING: A SYSTEMATIC LITERATURE REVIEW - Rakhmanita, Ani; Fahruri, Arief; Ikhsan, Muhammad (PT. Hafasy Dwi Nawasena, 2025)
Livestreaming presents itself as a new form of shopping environment that stimulates potential consumers in making stimulated shopping decisions. This paper aims to review the development of research related to livestreaming shopping using computational bibliometric analysis. Publish or Perish software was used to obtain literature data using the keyword